The potential effect of peel extracts of banana varieties: an in-vitro assessment - Alam, Faruk; Dutta, Avik; Ghosh, Alindam; Bora, Rinchi; Ghora, Soumya Sunder; Guchhait, Saurav; Mallick, Arijit (Journal of Applied Pharmaceutical Research, 2024)
Background: Assamese cuisine is known for its use of kolakhar, a traditional ingredient; Rhizome, the skin and stem of bananas, can be used to make it. An ash filter from a banana tree is used to produce antacids. The word: kol” or “kola” is a local term for banana. In Assam, India, kolakhar is a common food additive and traditional ingredient. Method: Water is filtered through banana tree ashes to create this. The banana peel is burned after it has been dried. The ash is subsequently blended with water and left overnight. The mixture is filtered through a fine cloth once the ash has settled to the bottom of the container by the following morning. Several studies were carried out by evaluating the preparation of peel extract, Physicochemical parameters, antioxidant activity, etc. followed by some analytical methods to find the biologically active components, potential uses, and additional benefits of banana peels beyond what they currently serve as waste products. Finally, an antimicrobial study was performed by using the disc diffusion method. In this study, 4 different types of banana species investigated sought to determine the antioxidant capacity, antimicrobial activity, FT-IR, and UV to determine which one is better. Result: The physicochemical parameters, analytical technique, and assay provide an overview of the chemical characteristics, phytoconstituents, and food safety of kolakhar, which contribute to its unique properties in both traditional medicine and culinary applications. Conclusion: In conclusion, depending on the banana type used, banana peel extracts exhibit considerable promise as organic antioxidants and antibacterial agents. Therefore, considering all parameters, we obtained various potential effects from this study. The results are discussed with a graphical representation of the banana peel extract.